Long Term Survival and Continued Complete Response of Vemurafenib in a Metastatic Melanoma Patient with BRAF V600K Mutation - K. Sahadudheen; Md. Rafiqul Islam; M. Iddawela (Case Reports in Oncological Medicine)
Introduction. BRAF kinase inhibitors such as Vemurafenib have shown improvement in overall survival, progression-free survival, and response rates in patients with metastatic melanoma with BRAF V600K mutation. However, there were no cases of complete remission reported in patients with V600K mutation before. Case Presentation. A 53-year-old man with metastatic melanoma and dialysis dependent end stage renal failure was treated safely with Vemurafenib for a BRAF V600K mutation positive melanoma and the case was reported elsewhere. After a long follow-up of the same patient treated with Vemurafenib, a complete radiological response was observed and the renal functions remained stable throughout the treatment. Main toxicities reported were grade 1 photosensitivity and skin cancers. Vemurafenib was discontinued but patient remains disease free 12 months after stopping treatment and the clinical review is ongoing. Conclusion. This is the first reported case of complete radiological response to a BRAF inhibitor in metastatic melanoma with BRAF V600K mutation and remains disease free even after discontinuation of treatment. This also shows clinical safety of Vemurafenib in end stage renal failure and highlights the need for closer look at the subgroup of patients with BRAF V600K mutation and its tumour biology.